2019
DOI: 10.1111/jog.13900
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia: The force of endometriosis

Abstract: Aim: Summarize recent findings of how hypoxia regulates numerous important processes to facilitate the implantation, proliferation and progression of ectopic endometriotic lesions. Methods: Most up-to-date evidences about how hypoxia contributes to the disease pathogenesis of endometriosis and potential therapeutic approaches were collected by conducting a comprehensive search of medical literature electronic databases. Quality of data was analyzed by experienced experts including gynecologist and basic scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 101 publications
2
33
0
Order By: Relevance
“…Hypoxia is an important factor of the endometriosis microenvironment (Becker et al, 2008;Wu, Hsiao & Tsai, 2019). Hypoxia can induce epigenetic changes in tumor cells, whereas hypoxia-induced epigenetic changes in endometriosis haven't been reported yet (Zhou et al, 2006;Shahrzad et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is an important factor of the endometriosis microenvironment (Becker et al, 2008;Wu, Hsiao & Tsai, 2019). Hypoxia can induce epigenetic changes in tumor cells, whereas hypoxia-induced epigenetic changes in endometriosis haven't been reported yet (Zhou et al, 2006;Shahrzad et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During this process, endometriosis is formed through complex survival processes such as steroidogenesis, angiogenesis, inflammation, and metabolic switches [41]. To withstand the hypoxic conditions, complex gene regulation is involved in endometriosis development [41]. Hypoxia is the main stimulus that activates AMPK [42,43].…”
Section: Accepted Articlementioning
confidence: 99%
“…Second, through the use of both in vitro and in vivo studies, we have provided convincing evidence that platelets are an unindicted culprit responsible for increased local production of estrogen, and that this is mainly through the induction of NF-κB and TGF-β1 signaling pathways. Third, our study provides evidence that activated platelets can directly induce a hypoxia state in endometriotic lesions, which subsequently cause further phenotypic changes 39 . Lastly, this study further underscores the importance of lesional microenvironment in shaping its fate.…”
Section: Discussionmentioning
confidence: 64%
“…These findings in wound healing raise a question as whether culprits other than endometriotic cells in the lesional microenvironment could also be responsible for the increased local estrogen production. Recent studies have shown that hypoxia, occurred to menstrual debris that is devoid of blood supply when regurgitated into the peritoneal cavity, can dramatically turn endometrial stromal cells into endometriotic counterpart, causing completely different phenotypes 39 . This notion may explain as why endometrial debris may invade and then establish itself in ectopic sites.…”
mentioning
confidence: 99%